P197 Efficacy of a Local Domiciliary Non-invasive Ventilation (NIV) Service for Motor Neurone Disease (MND): Patient Survival, Safety and Satisfaction. (12th November 2015) - Lane, A; Tollit, J; Lewis, R; Murray, P
Abstract : Background: NIV is an established treatment for MND patients with ventilatory failure and improves survival by an average of 219 days. 1 NHS England (2013) 2 recommend that MND patients are managed by complex weaning and ventilation centres. However, many patients find travel to hospitals difficult and distressing and therefore will not consider NIV. A Domiciliary NIV service was set up in April 2012 to provide integrated care in patients' homes. A small prospective audit was carried out to investigate survival rates, adverse events and satisfaction with the service. Method: Data were collected prospectively from 18 consecutive patients between April 2012 and June 2015 (169 weeks). NIV was started on onset of reported symptoms. All assessments, titration onto NIV and treatment was carried out in patients' homes. Results: 12 of 16 (75%) patients returned satisfaction questionnaires. 8 of 12 (67%) scored the service 10 (highly recommended) on the visual analogue scale, 4 patients left this blank. 100% responded that they had confidence and trust in the team and preferred to be seen at home. No adverse events were reported by these patients. Discussion: NIV survival with home based care is comparable with the current literature. Of the patients who died, the longest survival was 339 days, 60 days under median survival for those still alive. The reason for this is unclear but may be partly explained by 3 patients with bulbar involvement in this group. Further investigation into this cohort may reveal differences, such as long term feeding. Analysis is required to establish if home care is cost effective. Conclusion: MND patients requiring NIV can be safely and effectively managed in a home setting and find this preferable to hospital care. This patient centred model could increase the number of patients offered NIV, subsequently improving uptake. References: 1 Bourke S, Tomlinson M, Williams TL, et al . Effects of non-invasive ventilation on survival and quality of life in patients with amyotrophic lateral sclerosis: a randomised controlled trial. Lancet Neurol . 2006;5 :140–47 2 NHS England. NHS standard contract for respiratory: Complex home ventilation – adult. Service specification A14/S/a, 2013